ANALISA RASIO LIQUIDITAS TERHADAP PENILAIAN EFISIENSI MODAL KERJA PADA PT (Persero) KAWASAN BERIKAT NUSANTARA UNIT USAHA PELAYANAN LOGISTIK CAKUNG, JAKARTA UTARA - sabil sabil (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2015)
To find out how much the relationship between liquidity ratios with efficiency in assessing the financial position in KBN Logistics Services Unit in completing its obligations, for it is then necessary to use a tool called liquidity ratio analysis. From the calculation of this ratio is expected to help managers to assess the efficiency of working capital used by the company in business. To be able to assess the efficiency of working capital, the authors need the data in the form of a score or standard working capital efficiency, in 2009 the company has a current ratio of 65%, in 2010 the company has a current ratio of 78%, in 2009 the Company had a cash ratio of 6.92 %, while in 2010 the Company had a cash ratio of 7.04%, in 2009 the company has a quick ratio of 63.81%, while in 2010 the company has a quick ratio of 86.91%,From the calculation and analysis of ratios that had I use almost all of the use of working capital Logistics Services Business Unit is not efficient, which means Logistics Services Business Unit has been unable to meet its short-term liabilities with a working capital held in this case because the working capital business unit of service overall logistics are managed by a central office, for logistics services business unit manages only partially working capital alone. Keywords : Liquidity Ratio , Efficient Working Capital